Role of aluminium on the microstructure and corrosion behaviour of magnesium prepared by powder metallurgy method - Juliawati, Alias (Universiti Malaysia Pahang, 2020)
Much research on magnesium (Mg) emphasises creating good corrosion resistance of magnesium, due to its high reactivity in most environments. In this study, powder metallurgy (PM) technique is used to produce Mg samples with a variation of aluminium (Al) composition. The effect of aluminium composition on the microstructure development, including the phase analysis was characterised by optical microscope (OM), scanning electron microscopy (SEM) and x-ray diffraction (XRD). The mechanical property of Mg sample was performed through Vickers microhardness. The results showed that the addition of aluminium in the synthesised Mg sample formed distribution of Al-rich phases of Mg17Al12, with 50 wt.% of aluminium content in the Mg sample exhibited larger fraction and distribution of Al-rich phases as compared to the 20 wt.% and 10 wt.% of aluminium content. The microhardness values were also increased at 20 wt.% and 50 wt.% of aluminium content, comparable to the standard microhardness value of the annealed Mg. A similar trend in corrosion resistance of the Mg immersed in 3.5 wt.% NaCl solution was observed. The corrosion behaviour was evaluated based on potentiodynamic polarisation behaviour. The corrosion current density, icorr, is observed to decrease with the increase of Al composition in the Mg sample, corresponding to the increase in corrosion resistance due to the formation of aluminium oxide layer on the Al-rich surface that acted as the corrosion barrier. Overall, the inclusion of aluminium in this study demonstrates the promising development of high corrosion resistant Mg alloys.